Algorithms in clinical epilepsy practice: Can they really help us predict epilepsy outcomes?. Issue Volume 62:Issue S2(2021)Supplement (1st September 2020) - Jehi, Lara
Abstract: Significant technological advances have improved our ability to localize epilepsy and investigate the electrophysiology in patients undergoing preparation for epilepsy surgery. Conversely, our process of decision‐making and outcome prediction has remained essentially restricted to subjective clinical judgment. This may have hindered our ability to improve outcomes. In this review, we highlight the cognitive biases that interfere with medical decision‐making and present data on the use of algorithms and statistical models in general health care, before pivoting to discuss applications in the context of epilepsy.